Behavioral insomnia in a pediatric sleep clinic: restrospective study - Martins,Rosa (2020)
Background/Objective: Behavioral insomnia is a common sleep disorder among children, with potentially negative impact on health, behavior, and cognition. This study aimed to characterize a pediatric population referred to a Sleep Disorder Clinic of a tertiary hospital due to behavioral insomnia. Methods: Retrospective and descriptive study based on the review of medical records of patients with insomnia over an eight-year period (2008−2016). Results are presented as median (minimum-maximum), mean (standard deviation), and percentage. Results: A total of 964 children attended the Sleep Disorder Clinic in the considered time period, 162 (16.8%) of which due to insomnia and 137 (14.2%) to behavioral insomnia. Most children (58.4%) were male and the median age at referral was 45 months (5 months-18 years). The median bedtime was 10 pm (8 pm−4 am) and nocturnal awakenings were frequent, particularly in pre-school aged children. Regarding bedtime routines, 62% of children were not able to fall asleep alone, 48.9% had television in the bedroom, 43.1% (11.9% of which, teenagers) required an object to fall asleep, and 42.3% required lights on. Most patients (62%) had a routine to fall asleep, which was dependent on the caregiver in younger children and on television and reading in teenagers. The most frequent daytime symptoms were sleepiness in older children and irritability in younger children. Regarding treatment, 29.9% were taking drugs before referral. Conclusions: Most children in this study were preschoolers, an important age window. Later sleep time, TV in the bedroom, and parental dependence to fall asleep were frequent, revealing a broad area for intervention. The authors propose greater investment in training health professionals and caregivers working in the area, in order to promote the adoption of adequate sleep hygiene as a form of prevention.